The structure of the Earth’s crust of the central part of the Holovanivsk suture zone according to the reinterpretation of materials of IV geotraverse of DSS (PK 295—400) - Trypolsky, O.A.; Topoliuk, O.V.; Gintov, O.B. (Геофизический журнал, 2019)
The paper presents the results of reinterpretation of the materials obtained as a result of studies using the DSS method along the IV geotraverse at the site PK 295—400.